Предмет: Алгебра, автор: Хулиганка69

Упростите выражение:
а)(х+4)^2-7x
б)(с-1)^2-(1-2c)
в)(х-у)^2+х(у-х)
г)(а+b)^2-2b(a-b)
д)9m^2-(n-3m)^2
е)(a^2+b^2)-(a-b)^2
ж)z(5-z)+(z-5)^2
з)3u(u+2)-(u+3)^2

Ответы

Автор ответа: Аноним
0
(x+4)^2-7x=x^2+8x+16-7x=x^2+x+16\ \ (c-1)^2-(1-2c)=c^2-2c+1-1+2c=c^2\ \ (x-y)^2+x(y-x)=x^2-xy+y^2+xy-x^2=y^2\ \ (a+b)^2-2b(a-b)=a^2+2ab+b^2-2ab+2b^2=a^2+3b^2\\ 9m^2-(n-3m)^2=9m^2-n^2-9m^2+6mn=6mn-n^2\ \ (a^2+b^2)-(a-b)^2=a^2+b^2-a^2-b^2+2ab=2ab\ \ z(5-z)+(z-5)^2=5z-z^2+z^2-10z+25=25-5z\ \ 3u(u+2)-(u+3)^2=3u^2+6u-u^2-6u-9=2u^2-9
Похожие вопросы
Предмет: Обществознание, автор: Maksimondekarlo